PENGEMBANGAN PRODUK TEMPE BERBASIS KORO DI DESA BANJARSENGON, KECAMATAN PATRANG, JEMBER - Sony Suwasono; Jayus Jayus; Puspita Sari (LP2M Universitas Jember, 2022)
Patrang sub-district consists of 8 villages, namely Gebang, Jember Lor, Patrang, Baratan, Bintoro, Slawu, Jumerto, and Banjar Sengon. Banjarsengon Village is the farthest village from the Patrang District office + 7 km with an area of ​​about 14 km2. Until 2020, there are only a few food and beverage industries located in Patrang District, namely the shredded and milk industry in Gebang, and the tempeh industry in Baratan. However, there is no food and beverage industry in Banjar Sengon yet. This is very interesting because Banjar Sengon is a village that has the potential of human and natural resources. The tempeh industry is also not found, even though tempeh is widely consumed by the people in Banjar Sengon. Tempeh prices are getting more expensive in early 2022 due to high soybean prices. Due to the current difficulty in supplying expensive soybeans, several tofu and tempeh producers have begun to reduce production or stop production. This limitation of soybeans causes big problems for people who are usually consuming tofu and tempeh. Therefore, alternative types of koro beans must be provided to replace non-soybean raw materials. In this community service activity, the team has introduced koro beans as the raw material for making tempeh with a slight modification in the fermentation process. The results show that tempeh from koro gave high scores on performance, arome, taste, and texture, although the scores are still lower than soybean tempeh